(untitled) (World Science, 2020)
The periodic conduct of elections and the renewal of the electoral legislation attest to Ukraine’s emergence as a democratic and rule of law state. The purpose of the article is to analyze the constitutional-legal foundations of the exercise of the electoral rights of the Ukrainian citizens. It is noted that one of the oldest and most widespread and effective forms of direct democracy is elections, an institution of democracy that allows one to vote and be elected. However, it is noted that in Ukraine from 1991 to 2020 there were several independent electoral systems, which implies the use of proportional and majoritarian systems, as well as mixed ones − their varieties for holding different types of elections. The constitutional provisions stated in the article testify to the orientation of the Ukrainian society to ensure in Ukraine the implementation of the constitutional guarantees regarding the electoral rights of the citizens and the importance of this right, along with other guaranteed rights. Attention is paid to the Electoral Code of Ukraine, adopted on December 19, 2019, which is a codified legislative act that defines the guarantees of electoral rights of the citizens of Ukraine to participate in the formation of the composition of representative bodies of the state power, representative body of the Autonomous Republic of Crimea and representative bodies and elected officials of the local self-government of Ukraine, regulates the organization and holding of different types of elections.